Penerapan Aplikasi Sistem Informasi Penjualan Menggunakan Barcode - La Sudarman Darman; La Jejen; Muhammad Tasjiddin Teheni; Sarimuddin Sarimuddin (Abdimas Universal, 2023)
Along with the development of technology, many activities in the trade sector have used sales applications using barcodes. It aims to streamline time and be able to control data on sales and purchases of goods in a type of business. The purpose of this community service activity is to develop a sales information system application using a barcode so that users can easily input sales and purchase data for medicines, easily record stock cards and make reports on goods data as desired by the Baubau City Health Office and BPOM. The subject of this service activity is the owner of the Mentari Medika Pharmacy located in Lowu-Lowu Village, Lea-Lea District, Baubau City. This service activity systematically starts from needs analysis, application design, testing/implementation 1, testing/implementation 2, application \ to users and evaluation of activities and follow-up plans. The results of the activity indicate that after testing the application/implementation 1, it is necessary to add a menu to the application that is made so that application/implementation testing is necessary. In addition, this application is also equipped with a user manual, so that users are helped to operate this application.